Non-Material Value-Based Financial Management Practice of “Pappasang Tu Riolo” - La Ode Sumail Sumail; Ampauleng; Salma Abdullah (International Journal of Religious and Cultural Studies, 2023)
This article aims to interpret financial management practice based on local value namely Pappasang Tu Riolo without material character. By using the Nusantara paradigm, the research revealed the reality and emotional experiences of banana traders snack (pisang epe) on Losari beach, Makassar City. This study found that financial management with local wisdom values ​​in the form of Pappasang Tu Riolo is a unique character that is not found in conventional financial management concepts, which can present a new view of wisdom for financial management. As financial management is based on spiritual values, the traders can achieve sustainable financial performance as well as excellent socio-economic state though the pursuit of material gains have not become their main purpose.